UPTAKE AND BIOACCUMULATION OF WATER BORNE LEAD (Pb) IN THE FINGERLINGS OF A FRESHWATER CYPRINID, CATLA CATLA L. - M. S. Ahmed; S. Bibi (Journal of Animal and Plant Sciences, 2010)
A study was conducted to evaluate the uptake and accumulation of waterborne lead (Pb) in various tissues of Catla catla when exposed to lower doses.  Single breed fingerlings (6-8 cm) of C. catla were obtained from a commercial fish seed hatchery.  Six groups (in duplicate) of fish (40 each) were maintained at 22o C, pH 7.0, hardness 140 mg/l and DO 7.0 mg/l in 90 liters of water in glass tanks.  Each group was exposed to a sub-lethal dose of waterborne Pb at 0.0 mg/l, 1.0 mg/l, 2.5 mg/l, 5.0mg/l, 7.5 mg/l and 10.0 mg/l for 6 weeks. Fish sampling was done on day zero and weekly thereafter for six weeks.  Ten fish from each treatment were sacrificed; tissue samples were collected and prepared for analysis of Pb using graphite furnace atomic absorption spectrophotometer.  Fish tissues that were directly exposed to waterborne Pb, the absorption and accumulation was significantly high (p<0.05) in the skin (including mucus) (4.92 ±0.25 µg/g dry wt.), gills (4.71 ±0.33 mg/g dry wt.), and eyes (4.51 ±0.19 mg/g dry wt.), as compared to the tissues from control group.  While, Pb had accumulated significantly high (p<0.05) in internal tissues like liver (4.79 ±0.11 mg/g dry wt.), muscles (4.41 ±0.23 mg/g dry wt.) and intestine (4.21 ±0.22 mg/g dry wt.) as compared to the tissues from control group.  This study indicates that the fishes living in water bodies receiving industrial effluents and city waste water containing various heavy metals, had absorbed and accumulated in various tissues like skin, gills and intestine directly from water as well as alongwith the food during feeding.  With the passage of time as the fishes grow, these metals accumulate in various tissues like liver, muscles and intestine to a significantly high concentration not suitable for human consumption.
Keywords: Cyprinids; fish tissues; industrial effluents; Pb bioaccumulation; sub-lethal dose; topical absorption; water pollution